2009
DOI: 10.1007/s11671-009-9306-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Formation of the Head-to-Head Coalesced Szaibelyite MgBO2(OH) Nanowires

Abstract: The significant effect of the feeding mode on the morphology and size distribution of the hydrothermal synthesized MgBO2(OH) is investigated, which indicates that, slow dropping rate (0.5 drop s−1) and small droplet size (0.02 mL d−1) of the dropwise added NaOH solution are favorable for promoting the one-dimensional (1D) preferential growth and thus enlarging the aspect ratio of the 1D MgBO2(OH) nanostructures. The joint effect of the low concentration of the reactants and feeding mode on the hydrothermal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…4 reveals the porous structure. Previous works [ 24 , 25 ] by Zhu et al reported the better crystallinity of the MBH nanowhiskers than the present work; however, the synthesis mechanism in their work was quite different from our work. Besides the study of the synthesis mechanism in our work, the thermal annealing effect on the surface morphology and crystal structure of the MBH nanowhiskers synthesized with and without surfactants is also studied.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…4 reveals the porous structure. Previous works [ 24 , 25 ] by Zhu et al reported the better crystallinity of the MBH nanowhiskers than the present work; however, the synthesis mechanism in their work was quite different from our work. Besides the study of the synthesis mechanism in our work, the thermal annealing effect on the surface morphology and crystal structure of the MBH nanowhiskers synthesized with and without surfactants is also studied.…”
Section: Resultscontrasting
confidence: 91%
“…In addition, the conversion of magnesium borate hydroxide to anhydrous magnesium borate is rarely reported [ 7 , 21 ]. Zhu et al [ 8 , 24 , 25 ] reported the hydrothermal synthesis of MgBO 2 (OH) nanowhiskers using MgCl 2 , H 3 BO 3 and NaOH as the starting materials with molar ratio of Mg:B:Na as 2:3:4 at 240 °C for 18 h. Zhu et al [ 25 ] also investigated the effect of the dropping rate of NaOH into the precursor solution, droplet size, and amount of the NaOH solution and the hydrothermal reaction time on the hydrothermal formation of the MgBO 2 (OH) nanowhiskers with other synthesis parameters kept constant. The morphology preservation and crystallinity improvement in the thermal conversion of the hydrothermal synthesized MgBO 2 (OH) nanowhiskers to Mg 2 B 2 O 5 nanowhiskers was investigated in the temperature range of 650–700 °C and was kept under isothermal condition for 2.0–4.0 h [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mg 2 B 2 O 5 nanowires, 6-8 nanorods 9,10 and whiskers, [11][12][13] MgB 4 O 7 nanowires, 14 Mg 3 B 2 O 6 nanotubes 15 ) have been signicantly considered because of their excellent performances, when used as reinforcements in wide band gap semiconductors, 6 electronic ceramics, 14 antiwear additives, 16 and plastics or aluminum/ magnesium matrix alloys. 17 As a matter of fact, in addition to the traditional high temperature techniques, such as chemical vapor deposition (CVD) 6,9,10,14,15 and molten salt synthesis (MSS), [18][19][20] for anhydrous 1D magnesium borate nanoarchitectures, hydrated and anhydrous 1D magnesium borate nanorods/nanowires/nanowhiskers have also been synthesized by hydrothermal synthesis 8,[21][22][23] or thermal conversions based on hydrothermal systems (HTC). 12,24,25 Templated hydrothermal or solvothermal synthesis is widely used for hierarchical nanostructure fabrications, 2,26,27 but there are technical bottlenecks for the impurity introduction and the inevitable structural collapse during the post-treatments for template removal.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium borates can be used in ceramic industry, in superconducted material production, in detergent composition, in friction reducing additive manufacture, in fluorescent discharge lamps as luminescent material, in ferroelastic material production, in cathode ray tube screens, in X-ray screens, and as thermoluminescent phosphor [5][6][7][8][9][10]. And also magnesium borates have great potential in areas of electronic ceramics reinforcement, semiconductor material synthesis, and plastics or aluminum/magnesium matrix alloy production [11,12].…”
Section: Introductionmentioning
confidence: 99%